Strategi Branding Image Madrasah Untuk Membangun Trust Masyarakat - Sri Atin; Ika Fitriyati; Shaleh Shaleh (At-Ta'lim : Media Informasi Pendidikan Islam, 2023)
Abstract: Madrasah Image Branding Strategy to Build Community TrustThe branding image of an Islamic educational institution is absolutely needed in the midst of the increasing existence of an increasingly competitive madrasa. In addition, branding image is also carried out to improve the quality of education, where madrasas are often underestimated by the community. This study aims to determine the branding strategy of madrasah image in buildingtrust. This study used descriptive qualitative method. This method is used to describe the strategy of branding image in Madrasah Ibtidaiyah Ma'arif Giriloyo 1 Bantul based on data obtained from madrasas and users of educational services. Informants from this study were principals, teachers, and parents of students. The informant selection technique in this study, the researcher used purposive sampling technique. Data collection techniques in this study used document analysis techniques, in-depth interviews, and observation. The method used to check the validity of the data is the triangulation method of data source. The stages in analyzing the data in this study are data reduction, data presentation, and drawing conclusions. The results show that: the branding strategy that has been carried out by the Head of Madrasah is to apply the Marketing Mix 7P Product, Place, Promotion, Price, People, Physical Evidence, and Process. In the future, further research is expected to be able to discuss in depth related to the effect of the effectiveness of the branding strategy applied by madrasas.Abstract: Strategi Branding Image Madrasah Untuk Membangun Trust Masyarakat.Branding image sebuah lembaga pendidikan Islam sangat diperlukan ditengah meningkatnya eksistensi madrasah yang semakin kompetitif. Selain itu branding image juga dilakukan demi peningkatan mutu pendidikan, yang mana madrasah sering dipandang sebelah mata oleh masyarakat. Penelitian ini bertujuan untuk mengetahui strategi branding image madrasah dalam membangun kepercayaan (trust) masyarakat. Penelitian ini menggunakan metode deskriptif kualitatif. Metode ini digunakan untuk mendeskripsikan strategi branding image di Madrasah Ibtidaiyah Ma’arif Giriloyo 1 Bantul berdasarkan data yang diperoleh dari madrasah dan pengguna jasa pendidikan. Informan dari penelitian ini adalah kepala sekolah, guru, dan orangtua peserta didik. Teknik pemilihan informan dalam penelitian ini, peneliti menggunakan teknik purposive sampling. Teknik pengumpulan data dalam penelitian ini menggunakan teknik analisis dokumen, wawancara mendalam, dan observasi. Metode yang digunakan untuk memeriksa keabsahan data adalah metode triangulasi sumber data. Tahapan dalam menganalisis data dalam penelitian ini adalah reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: strategi branding yang telah dilakukan oleh Kepala Madrasah adalah dengan menerapkan bauran pemasaran (Marketing Mix) 7P yaitu Product, Place, Promotion, Price, People, Physical Evidence, dan Process. Kedepannya penelitian selanjutnya diharapkan dapat membahas secara mendalam terkait dengan pengaruh efektivitas strategi branding yang diterapkan oleh madrasah.